Green Central Banking, Sustainable Finance, and Monetary Policy in Emerging Economies: Policy Lessons from a Systematic Review - Muhammad Putra Aprullah; Muhammad Arfan; Yossi Diantimala; Irsyadillah Irsyadillah; Sofyan Syahnur; William Ben Gunawan (Institute of Multidisciplinary Research and Community Service, 2026)
This paper aims to analyze the green central banking role in transforming sustainable finance and monetary policy in emerging economies. In particular, it examines changes in the integration of climate risk and opportunity into monetary policy mandates, regulatory approaches, and financial intermediation functions while also evaluating the institutional characteristics that facilitate or hinder these efforts. Methodologically, a PRISMA-based systematic literature review of 85 Scopus-indexed articles was conducted to identify key themes, policy pathways, and emerging debates surrounding green central banking and climate risk management in developing/EM countries within the broader global landscape of sustainable finance. The results indicate five overarching patterns. For starters, central banks seem to be extending their policy mandates well beyond normal price stability to combat climate-induced systemic risks. Second, physical and transition risks are slowly being incorporated into monetary policy, macroprudential regulation, and supervisory norms. Third, green bonds and other sustainable financial instruments continue to expand their role as a programming instrument working by reallocating capital from carbon-intensive investments to environmentally sustainable or low-carbon activities. Fourth, institutional quality, regulatory capacity, and inter-sectoral policy coordination play an instrumental role in promoting green finance initiatives. Fifth, green central banking has significant potential to bolster long-term financial stability while supporting low-carbon transitions. However, its real-world impacts are limited by data availability, uneven institutional readiness, and substantial practical disparities across emerging economies. This paper connects climate risk, sustainable finance, and monetary policy into a common narrative that offers both an academic contribution to the literature and policy implications for central banks and policymakers seeking to enhance climate-responsive financial governance in developing countries. Keywords: green central banking, sustainable finance, climate risk, monetary policy, financial stability.